2019
DOI: 10.1002/pen.25088
|View full text |Cite
|
Sign up to set email alerts
|

A heuristic method for modeling the initial pressure drop in melt filtration using woven screens in polymer recycling

Abstract: This paper addresses the use of heuristic optimization algorithms to generate generally valid analytic equations for estimating the initial pressure drop of square and Dutch woven screens in polymer recycling. We present a mathematical description of the isothermal initial pressure drop of non-Newtonian polymer melt flows through woven screens without the need for numerical methods. We first performed numerical CFD simulations to create a set of 9,000 physically independent modeling set-ups as a basis for heur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…The literature provides some coverage of processing related aspects of melt filtration systems in polymer processing [ 76 ] and recycling [ 38 , 39 , 76 ]. Methods for calculating the pressure drop at the filter, the average residence time of the melt within the filter, or the self-cleaning efficiency [ 77 , 78 ], can be found there. Furthermore, it has been shown that melt filtration of recycled post-consumer PP is key to achieve higher performance levels, e.g., in solid-state drawing [ 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…The literature provides some coverage of processing related aspects of melt filtration systems in polymer processing [ 76 ] and recycling [ 38 , 39 , 76 ]. Methods for calculating the pressure drop at the filter, the average residence time of the melt within the filter, or the self-cleaning efficiency [ 77 , 78 ], can be found there. Furthermore, it has been shown that melt filtration of recycled post-consumer PP is key to achieve higher performance levels, e.g., in solid-state drawing [ 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…The addition of a filter helps remove unwanted non-volatile contaminants from the plastic and increases the mechanical properties of the recycled plastic. 176 When selecting recycling technologies in manufacturing processes, it is important to select the appropriate mechanism to minimize the degradation of the plastic for highquality new parts. 159…”
Section: Innovation In Extrusion Technologiesmentioning
confidence: 99%
“…[ 33,36,37 ] Melt filters are chosen according to specific extrusion contamination and can include screen‐changers such as slide plates, woven screens, or filter cartridges. [ 38,39 ] Lengthening extruders must be balanced against the increase in system dwell times that can exacerbate chain scission. Recycling systems must be designed with consideration to specific degradation mechanisms.…”
Section: Introductionmentioning
confidence: 99%